2019
DOI: 10.21203/rs.2.9515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial profile and their antibiotic resistance patterns from blood culture in Intensive Care Unit patients at the University Of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia.

Abstract: Background: The burden of bloodstream infection and antibiotic resistance in intensive care unit (ICU) is high when compared with other settings. The data on the changing antibiotic resistance trends are important for infection control activities. There is no sufficient data in the intensive care units of this hospital. Objective: The aims of this study were to assess the magnitude and risk factors of bacterial pathogens and their antibiotic resistance patterns of blood culture isolates from ICU patients at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Also, K. pneumoniae (28.6%) was the second reported GNB, and it is relatively similar to the fnding of a previous study conducted in Zimbabwe 20.3% [42]. But, it is higher than those of the studies carried out in Uganda 13% [35], Hiwot Fana 12.4% [41], Mizan-Tepi 14.8% [36], Namibia 3% [30], Northern Nigeria 2.4% [40], Mekelle 8% [27], and Gondar 4.08% [34]. Tis potential variation might be due to the dissemination of K. pneumoniae throughout the ICU environments during cleaning and recontamination of HCP hands with isolates during patient's examinations, handcontact made with patients or inanimate surfaces, and handwashing.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Also, K. pneumoniae (28.6%) was the second reported GNB, and it is relatively similar to the fnding of a previous study conducted in Zimbabwe 20.3% [42]. But, it is higher than those of the studies carried out in Uganda 13% [35], Hiwot Fana 12.4% [41], Mizan-Tepi 14.8% [36], Namibia 3% [30], Northern Nigeria 2.4% [40], Mekelle 8% [27], and Gondar 4.08% [34]. Tis potential variation might be due to the dissemination of K. pneumoniae throughout the ICU environments during cleaning and recontamination of HCP hands with isolates during patient's examinations, handcontact made with patients or inanimate surfaces, and handwashing.…”
Section: Discussionsupporting
confidence: 74%
“…Te results of our study showed that varied groups of bacteria, including both Gram-positive (56%) and Gramnegative (44%) bacteria contaminated the ICU environments. Comparable to our results, the frequency of Grampositive bacteria constituted the leading inhabited bacteria compared to Gram-negative bacteria in diferent countries, for example, in Iran (60.7% vs. 39.3%) [33], Nigeria (52.2% vs. 47.8%) [28], and Gondar in Ethiopia (60.5% vs. 39.5%) [34]. Te dominance of Gram-positive over Gram-negative bacteria could be described by the fact that Gram-positive bacteria, being free of lipid-dominant drying up prone outer membrane, have concerning nature ability to keep their viability on diferent hospital environments for several time periods [33].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The included studies were conducted in four regions (Amhara, Tigray, Oromia, and Southern Nations, Nationalities, and Peoples' Region (SNNPR)) and from the two self-administrative cities (Addis Ababa and Dire Dawa). Of the 26 studies that fulfilled the review inclusion criteria [ 7 , 11 , 14 , 16 , 35 , 36 , 38 – 52 , 55 ], eleven studies were conducted in Amhara region [ 7 , 8 , 11 , 14 , 36 , 40 , 44 , 45 , 52 – 54 ], nine in Addis Ababa [ 16 , 41 , 43 , 46 , 48 – 50 , 55 , 56 ], three in Oromia region [ 35 , 38 , 42 ], and a single study from Tigray [ 39 ], Dire Dawa [ 51 ], and SNNPR [ 47 ]. The sample size of individual studies ranged from 83 [ 53 ] to 856 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intensive care units (ICUs) are the most life-saving facilities in hospitals, with highly specialized clinicians and nurses caring for severely ill patients. Most conditions treated in ICU are life-threatening, severe injuries and illnesses that necessitate regular monitoring and support from specialist technology and pharmaceuticals to ensure normal body processes ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%